Setting targets for local authorities to increase their capacity to develop and implement sustainable transport measures - Kalakou, S.; Pirra, M.; Diaz, A.; Spundflash, S. (Capacity building in local authorities for sustainable transport planning, 2023)
In order to assist cities with the implementation of their mobility plans, it is essential to analyze which factors influence their capacity to plan, develop and implement mobility measures. To achieve this, a four-step process was carried out together with the cities involved in the project. In the first step a comprehensive characterisation and contextualisation survey was conducted to assess the context of the cities as well as their actual situation in terms of mobility plans. Then, each of the six partner cities self-assessed its capacity to implement mobility plans according to a set of capacity indicators relevant to organizational, legal, political and societal aspects involved in any city´s operations. The results of this self-assessment indicated the areas on which each City Authority should focus in order to improve its capacity to implement in general mobility plans. At the last step, each city focused on the mobility plans that are regarded as priorities and a link between these plans and the capacity indicator targets were made. The result of this process was the set of specific capacity indicator targets for each city assisting the stakeholders to identify which part of their operation needs to be endorsed in order to successfully apply the prioritized mobility plans. The four-step approach presented in this chapter is a transferable tool that can be applied by City Authorities in order to understand and prioritize their capacity needs in transport departments.